2023
DOI: 10.1002/anie.202217958
|View full text |Cite
|
Sign up to set email alerts
|

A Triptycene‐Based 2D MOF with Vertically Extended Structure for Improving the Electrocatalytic Performance of CO2 to Methane

Abstract: Two‐dimensional conductive metal‐organic frameworks (2D‐c‐MOFs) have attracted extensive attention owing to their unique structures and physical‐chemical properties. However, the planarly extended structure of 2D‐c‐MOFs usually limited the accessibility of the active sites. Herein, we designed a triptycene‐based 2D vertically conductive MOF (2D‐vc‐MOF) by coordinating 2,3,6,7,14,15‐hexahydroxyltriptycene (HHTC) with Cu2+. The vertically extended 2D‐vc‐MOF(Cu) possesses a weak interlayer interaction, which lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 75 publications
(5 reference statements)
1
29
0
Order By: Relevance
“…Currently, many research studies have demonstrated that the polyanion type Na 3 V 2 (PO 4 ) 2 O 2 F (NVPF) electrode is a Zn 2+ host to store Zn 2+ ions at high voltage reversibly 32 . In Figure 5A, through the typical charge–discharge profiles of NVPF cathode and p‐MoSe 2 anode, the output voltage of p‐MoSe 2 ||Zn x NVPF rocking chair cell can be estimated at around 0.8 V, which reaches the general level of most of the Zn metal batteries (Zn||V‐O systems) 35–37 . Based on the total mass of cathode and anode, the capacities of 84.8, 62.1, 43.5, 37.3, 35.5, and 28.1 mAh g −1 are displayed at 40, 60, 100, 160, 200, and 400 mA g −1 , respectively (Figure 5B,C), corresponding to the maximum energy density of 68 Wh kg −1 .…”
Section: Resultsmentioning
confidence: 96%
“…Currently, many research studies have demonstrated that the polyanion type Na 3 V 2 (PO 4 ) 2 O 2 F (NVPF) electrode is a Zn 2+ host to store Zn 2+ ions at high voltage reversibly 32 . In Figure 5A, through the typical charge–discharge profiles of NVPF cathode and p‐MoSe 2 anode, the output voltage of p‐MoSe 2 ||Zn x NVPF rocking chair cell can be estimated at around 0.8 V, which reaches the general level of most of the Zn metal batteries (Zn||V‐O systems) 35–37 . Based on the total mass of cathode and anode, the capacities of 84.8, 62.1, 43.5, 37.3, 35.5, and 28.1 mAh g −1 are displayed at 40, 60, 100, 160, 200, and 400 mA g −1 , respectively (Figure 5B,C), corresponding to the maximum energy density of 68 Wh kg −1 .…”
Section: Resultsmentioning
confidence: 96%
“…[1] The combination of the conjugated building blocks and appropriate metal nodes is of great importance for the successful construction of 2D c-CPs The ligands include hexahydroxytriphenylene (HHTP), [7] benzenehexathiol (BHT), [8] hexaiminotriphenylene (HITP), [9] triphenylenehexathiol (HTTP), [10] hexaiminobenzene (HIB), [11] hexahydroxybenzene (HHB), [12] perthiolatedcoronene (PTC), [13] benzenehexaseleno (BHS), [14] hexahydroxytrinaphthylene (HHTN), [15] dibenzochryseneoctaol (DBC), [16] phthalocyanine (Pc), [17] hexaiminotrinaphthylene (HITN), [18] hexahydroxyltruxone (HHTXO), [19] hexaazatrinaphthylene (HATNA), [20] and hexahydroxyltriptycene (HHTC). [21] and the regulation of their electronic performances. The symmetric structure of the ligand usually determines the final topology of the 2D c-CPs.…”
Section: Topological Structures Of 2d C-cpsmentioning
confidence: 99%
“…Timeline of important events in the development of 2D c-CPs. The ligands include hexahydroxytriphenylene (HHTP),[7] benzenehexathiol (BHT),[8] hexaiminotriphenylene (HITP),[9] triphenylenehexathiol (HTTP),[10] hexaiminobenzene (HIB),[11] hexahydroxybenzene (HHB),[12] perthiolatedcoronene (PTC),[13] benzenehexaseleno (BHS),[14] hexahydroxytrinaphthylene (HHTN),[15] dibenzochryseneoctaol (DBC),[16] phthalocyanine (Pc),[17] hexaiminotrinaphthylene (HITN),[18] hexahydroxyltruxone (HHTXO),[19] hexaazatrinaphthylene (HATNA),[20] and hexahydroxyltriptycene (HHTC) [21].…”
mentioning
confidence: 99%
“…were applied in gas absorption and removing harmful organic vapor or other materials. However, these sorbents generally undergo the defects of weak interaction, limited micropore structure, or being moisture-sensitive and thus hinder their practical applications . As for organic porous sorbents, microporous organic polymers (MOPs) are deemed promising porous sorbents due to their microporous-rich structure, superior physicochemical stability, high specific surface area, tunable surface chemistry, and plentiful varieties, which have been widely applied in CO 2 and toxic gas adsorption. To obtain advanced MOP materials, three-dimensional (3D) rigid building blocks were utilized to design and construct 3D MOPs with a higher specific surface area and porosity. , …”
Section: Introductionmentioning
confidence: 99%